2021
DOI: 10.1159/000515168
|View full text |Cite
|
Sign up to set email alerts
|

Medical Adjuvants in the Treatment of Surgically Refractory Arteriovenous Malformations of the Head and Face: Case Report and Review of Literature

Abstract: <b><i>Background:</i></b> Arteriovenous malformations (AVMs) of the brain and face present unique challenges for clinicians. Cerebral AVMs may induce hemorrhage or form aneurysms, while facial AVMs can cause significant disfigurement and pain. Moreover, facial AVMs often draw blood supply from arteries providing critical blood flow to other important structures of the head which may make them impossible to treat curatively. Medical adjuvants may be an important consideration in the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…MEK inhibitors: sirolimus (rapamycin), selumetinib, and trametinib 127,128 bAVM indicates brain arteriovenous malformation; SMAD4, mothers against decapentaplegic homolog 4; and VEGF, vascular endothelial growth factor.…”
Section: Animal Models Of Bavmsmentioning
confidence: 99%
“…MEK inhibitors: sirolimus (rapamycin), selumetinib, and trametinib 127,128 bAVM indicates brain arteriovenous malformation; SMAD4, mothers against decapentaplegic homolog 4; and VEGF, vascular endothelial growth factor.…”
Section: Animal Models Of Bavmsmentioning
confidence: 99%
“…Įvairių tyrimų duomenimis, arterioveninės malformacijos nereaguoja į gydymą su sirolimu [4,7]. Vis dėlto, literatūroje galima rasti atvejų aprašymų, parodančių, kad mTOR inhibitorių vartojimas gali užkirsti kelią patologijos recidyvavimui po intervencijos [8].…”
Section: Tyrimo Rezultataiunclassified
“…Aside from this, non-steroid anti-inflammatory drugs, analgesics, and low molecular weight heparin are used as the treatment of AVM patients. [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, various studies have reported that angiogenesis induced under hypoxia was effectively compared and evaluated in normal and pathophysiological situations using the CD31 expression [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%